Proprotein convertase subtilisin/kexin type 9 is related to disease activity and damage in patients with systemic erythematosus lupus - Sánchez-Pérez, Hiurma (Ther Adv Musculoskelet Dis, 2020)
BACKGROUND: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease that regulates cholesterol metabolism through low-density lipoprotein receptor degradation and that has been linked to cardiovascular (CV) disease. The purpose of the present study was to examine whether PCSK9 levels are disrupted compared with controls in patients with systemic lupus erythematosus (SLE). We additionally sought to establish whether PCSK9 is related to both the abnormalities in the lipid profile and to the disease activity or damage of patients with SLE. METHODS: We performed a cross-sectional study that encompassed 366 individuals: 195 SLE patients and 171 age-, sex-, and statin intake-matched controls. PCSK9, lipoproteins serum concentrations, and lipid profiles were assessed in patients and controls. A multivariable analysis, adjusted for standard CV risk factors, was performed to evaluate the role of PCSK9 in SLE-related dyslipidemia. RESULTS: Most lipid related-molecules were decreased in patients with SLE compared with controls. This downregulation included PCSK9, with PCSK9 levels being lower in patients than controls in the full multivariable analysis, including the modifications in lipid profiles that the disease itself produces {beta coefficient –73 [95% confidence interval (CI) –91 to –54] ng/ml, p ⩽ 0.001}. Both SLICC and SLEDAI scores were independently and positively related to PCSK9. Patients currently on hydroxychloroquine exhibited decreased levels of PCSK9 compared with those that were not taking hydroxychloroquine [beta coefficient –30 (95% CI −54 to −6) ng/ml, p = 0.015]. CONCLUSION: PCSK9 is downregulated in SLE compared with controls, but SLE patients with higher disease activity and damage exhibited higher PSCK9 serum levels.